Respuestas

2012-06-29T00:58:51+02:00

 5x-y=9     ------------> x+2y=4

                                 x+2(5x-9)=4

                                 x+10x-18=4

                                 11x=22

                                 x=2

y=5x-9

   

5(2)-y=9

10-9=y

y=1                       

2012-06-29T02:17:34+02:00

5x-y=9     ------------> x+2y=4

                                 x+2(5x-9)=4

                                 x+10x-18=4

                                 11x=22

                                 x=2

y=5x-9

   

5(2)-y=9

10-9=y

y=1